2011
DOI: 10.4067/s0716-97602011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Elevated yield of Monacolin K in Monascus purpureus by fungal elicitor and mutagenesis of UV and LiCl

Abstract: In China, Monascus spp., a traditional fungus used in fermentation, is used as a natural food additive. Monascus spp. can produce a secondary metabolite, monacolin K namely, which is proven to be a cholesterol-lowering and hypotensive agent. Hence, recently, many researchers have begun focusing on how to increase the production of monacolin K by Monascus purpureus. In the present study, we investigated the effect of the fungal elicitor and the mutagenesis of UV & LiCl on the amount of monacolin K produced by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…UV irradiation for 45s was performed under 1.0% LiCl conditions, then five mutant strains were obtained after three rounds of irradiation. M. purpureus ZT35, a strain with high MK yield, was obtained through five generations of culture, which has a MK yield that is three times higher than that of the original strain [15]. In addition, MK synthesis by Monascus has a competitive relationship with the synthesis of red pigment.…”
Section: Monascus Strain Breeding For High-yield Mk Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV irradiation for 45s was performed under 1.0% LiCl conditions, then five mutant strains were obtained after three rounds of irradiation. M. purpureus ZT35, a strain with high MK yield, was obtained through five generations of culture, which has a MK yield that is three times higher than that of the original strain [15]. In addition, MK synthesis by Monascus has a competitive relationship with the synthesis of red pigment.…”
Section: Monascus Strain Breeding For High-yield Mk Productionmentioning
confidence: 99%
“…The MK yield of Monascus stabilizes when it is fermented to 12-18d [13,24,40], and the optimum fermentation time is usually 14-15d [17,54,56]. As the fermentation time goes on, MK content will reach the peak value followed by a decreasing trend [15,62]. Therefore, it is recommended to control the fermentation time of MK production by Monascus to about 15d.…”
Section: Fermentation Timementioning
confidence: 99%
“…Meanwhile, the highest absorbance of monacolin K of MFR which inoculated by YES and YMP inoculum was obtained on the 10 th day (Figure 3b and c). However, the ratio of monacolin K/citrinin absorbances of MFR which produced by MSG ino- [14], and citrinin was detected at maximum wavelength 500 nm [15]. Based on the data on figure 3, MFR which produced by MSG inoculum on the 8 th day was selected for detoxification process by 0.1, %f H 2 O 2 .…”
Section: Analysis Of Citrininmentioning
confidence: 99%
“…Bühler et al (2015) observed that light intensity is an essential factor in the mycelium growth and pigment production of Monascus. Indeed, monacolin K produced by ultraviolet (UV)-irradiated Monascus was three times greater than the control culture (Sun et al 2011). Monacolin K, commercially known as lovastatin, is a potent competitive inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, inhibits cholesterol biosynthesis, and lowers blood cholesterol levels in both humans and animals.…”
Section: Introductionmentioning
confidence: 99%